Analisa Status Halal Produk Umkm Perspektif Fatwa Mui Nomor 4 Tahun 2003 Tentang Standardisasi Fatwa Halal: Studi Kasus UMKM At-Tarqiyah, UD. Nayla Az-Zahrah, Dapur Aim Talang Siring Di Kabupaten Pamekasan - Harisah, Harisah; Almasuniyah, Annuriyah (Al-Hiwalah: Journal of Sharia Economic Law, 2023)
Many MSME producers of processed food put halal writing on the packaging, either only with ordinary Latin and Arabic writing, or accompanied by the MUI halal logo and in terms of the main raw materials or additional ingredients, it is difficult to declare the origin of the ingredients to be halal. In fact, the clarity of a food product is the most important thing so that consumers know that the product they are consuming is a halal product and the origin of the ingredients is clear. This study uses a type of normative legal research with a statute approach and a textual approach. This research was approved to be conducted on 19 November 2021, while this research took place on 1 March 2022 BPJPH established a new halal label that applies nationally. For this reason, with this stipulation there is a transfer of the authority of the institution that issues halal certificates from the LPPOM-MUI institution to BPJPH under the Ministry of Religion, this design change is part of the transfer of authority for halal certificates to BPJPH. The results of the study show that: First, the production activities of the three SMEs in Pamekasan, namely UD. Nayla AZ, Kitchen AIM Talang Siring, in the process of procuring materials to distribution, which was carried out in practice, there were no activities and facilities contaminated with unclean/unlawful objects, apart from that no critical activities were found that could cause a product to be unlawful. Whereas at Tarqiyah in its critical activity it was found that the use of raw materials in the form of petis did not have a halal label. Second, the results of the analysis that the researchers carried out using MUI fatwa No. 4 of 2003 concerning the standardization of halal fatwa indicates that MSME products at Tarqiyah, namely BAPER, do not comply with 100% halal principles in accordance with LPPOM-MUI principles. Because the raw materials used are not labeled halal, so the origin of the materials, processes, and facilities used is not known, not only that, materials that are not labeled halal are also included in critical activities that cause a product to be non-halal.